2020
DOI: 10.3389/fpubh.2020.00234
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Is Iron Supplementation During Pregnancy and Childhood in Reducing Anemia Among 6–59 Months Old Children in India?

Abstract: Objectives: The study sought to identify whether iron and folic acid supplementation of pregnant women and preschool children is associated with child's anemia status and the predictors of anemia among children in India. Design: Secondary data analysis was performed using the National Family Health Survey 4 data. Multivariable logistic regression was used to identify the adjusted associations between child's anemia status and iron supplementation, both during pregnancy and childhood. Also, a model of significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Our study found that a higher level of maternal education and residence in economically developed areas were associated with lower odds of developing anaemia. This observation is in concordance with findings from Ghana [ 21 ], Guinea [ 22 ], India [ 23 , 24 ] and other studies in China [ 25 ]. Although the socioeconomic indicators for China (e.g., food expenditure, average disposable income and gross domestic product per capita) have increased in both urban and rural areas over the past decades [ 26 , 27 ], holistic socioeconomic conditions remain better in urban and Eastern/Central areas than in rural and Western areas [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found that a higher level of maternal education and residence in economically developed areas were associated with lower odds of developing anaemia. This observation is in concordance with findings from Ghana [ 21 ], Guinea [ 22 ], India [ 23 , 24 ] and other studies in China [ 25 ]. Although the socioeconomic indicators for China (e.g., food expenditure, average disposable income and gross domestic product per capita) have increased in both urban and rural areas over the past decades [ 26 , 27 ], holistic socioeconomic conditions remain better in urban and Eastern/Central areas than in rural and Western areas [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have demonstrated that maternal and reproductive health (e.g., premature birth, LBW, low maternal birth age) are associated with a higher risk of developing childhood anaemia [ 23 , 29 , 30 ]. Consistent with these results, our study showed that these risk factors were strongly associated with higher odds of developing anaemia among Chinese infants aged 0–23 months.…”
Section: Discussionmentioning
confidence: 99%
“…A positive association between the proportion of three or four births in 5 years and childhood anemia was observed in the districts of Gujarat, Maharashtra, Goa, Karnataka, and Kerala. As reported by Thomas et al, 18 children in the anemic group had higher mean birth order compared with those in the nonanemic group. With each unit increase in the birth order, a child was at a 3.0% increased likelihood of being anemic.…”
Section: Discussionsupporting
confidence: 64%
“…Varghese et al 17 attribute this continuing burden of anemia to dietary and environmental reasons. Thomas et al 18 reported a significant association between supplementation during pregnancy and child's anemia status. Based on the results in our study, districts belonging to Kerala, Himachal Pradesh, and Jammu & Kashmir showed a highly negative association between proportion of mothers who consumed IFA for 100 days or more when they are pregnant and the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation